Memaksimalkan Fotografi untuk Desain Web - Kadek Satria Adidharma (Humaniora, 2013)
Article aims at looking clearly about the development of photography industry in the Internet world in general and in web design ini specific. Article discussed how the development of the needs of photography since the early beginning of web 1.0 to the advanced development of downloading process. Without limitation, there will be guarantee that there are lots of web designer having free mind to design different and intriguing web page.